Gender Violence Against Indonesian Women in Ziggy Zezsyazeoviennazabrizkie’s Tiga dalam Kayu: A Feminist Literary Analysis - Wini Iga Munggarani; Rudi Adi Nugroho; Yulianeta, Yulianeta (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose: This research aims to analyze the representation of violence against women in  Indonesia as depicted in the novel Tiga Dalam Kayu by Ziggy Zezsyazeoviennazabrizkie. The  study seeks to explore how social constructions often perpetuate violence against women in  Indonesia from a feminist perspective. This research is grounded in the pervasive issue of  violence against women in Indonesia, encompassing cases of domestic violence, sexual abuse,  and even murder. Methodology: The study employs a descriptive qualitative method with a  literature review approach to achieve its objectives. Mansour Fakih’s theory of gender-based  violence is utilized to analyze the portrayal of violence against women in the novel. Main  Findings: The findings reveal five distinct types of violence against women represented in  Tiga Dalam Kayu: one instance of pornography, three instances of rape, five instances of  physical violence, one instance of prostitution, and one instance of sexual harassment. These  depictions of violence are shaped by historical and cultural contexts, alongside the deeply  rooted patriarchal values that persist within Indonesian society. Applications: The study  highlights how literature serves as a medium to capture and portray the harsh realities of human  experiences, particularly the challenges faced by women. Novelty/Originality of This Study: The study underscores the novelist's effort to represent the suffering endured by Indonesian  women due to the prevalence of violence in their lives. By examining these portrayals, this  research provides a deeper understanding of how literature reflects societal issues and  challenges patriarchal norms.
Keywords: Feminist literature; gender equality; sociology of literature; women's violence